Analisis Perilaku Belanja Impulsif Gen Z di Tiktok Shop - Noprella Azura Zeta; Muhammad Najib; Erwin Permana; Lazarus Sinaga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
TikTok has transformed into an effective digital marketing platform, not only for introducing products but also for shaping impulsive shopping behavior. This study aims to analyze the impulsive shopping behavior of Generation Z on TikTok Shop. The research was conducted using a qualitative descriptive approach, with data obtained from digital searches and observations. The findings indicate that Generation Z has a strong interest in utilizing the TikTok Shop feature within the TikTok application, making it one of their preferred alternatives for online shopping transactions. TikTok significantly influences Generation Z’s shopping behavior, as they tend to purchase products after seeing them on the platform. Businesses leverage TikTok as an efficient marketing tool, particularly through creative content, short videos, and influencer recommendations. By utilizing an algorithm that tailors content to users’ preferences, TikTok Shop creates offers that appear attractive to consumers. Generation Z is often influenced to buy items they do not actually need. Sudden purchases driven by emotions—such as low prices or limited-time offers—often lead them to overlook product quality. As a generation living in the digital era, Gen Z needs to better regulate their impulsive consumer behavior. Wisely utilizing technology and understanding the marketing strategies used by platforms like TikTok Shop can help them avoid excessive impulsive spending. By prioritizing needs over wants and carefully considering the value and benefits of a product before purchasing, Gen Z can become smarter and more responsible consumers.